Analysis of Conical Part of Integrally Wound Composite Pressure Vessel Subjected to Internal Pressure and Temperature Loading - Padovec Zdeněk (Journal of Mechanical Engineering)
The presented article focuses on membrane solution of conical part from integrally wound conical pressure vessel. Wall of cone consist of three layers with (90/±ω0/90) symmetrical lay-up. Combination of netting theory and theory of orthotropic continuum was used for stress analysis. The cone was loaded by internal pressure and uniform temperature change. Obtained results for both loading cases were compared with the results from Finite Element Method (FEM) with achieving good agreement.